3D numerical investigation of energy transfer and loss of cavitation flow in perforated plates. Issue 1 (1st January 2020) - Xu, Xiaogang; Fang, Liang; Li, Anjun; Wang, Zhenbo; Li, Shuxun
ABSTRACT: Perforated plates are prevalently used in various integrated energy systems for flow restriction, vibration, and noise reduction. The characteristics of flow energy transfer and loss in perforated plates have a significant impact on its piping systems. The existing design and previous studies largely paid little attention to the characteristics of flow energy variation, resulting in severe performance issues and energy consumption. In this study, the characteristics of energy transfer and loss of cavitation flow with various pressure ratios in single and multi-stage perforated plates were numerically studied. The parameters of energy ratio and energy gradient were developed to effectively evaluate the degree and rate of flow energy variation. Results showed that the contribution to energy loss generated from orifice outlet was relatively larger than the inlet and that the degree and rate of energy variation deceased with the increasing stages during the flow in multi-stage models. Additionally, increased stages of perforated plate resulted in a multi-stage stepped energy drop in throttling orifices, and lead to obvious suppression of the cavitation. This work intends to provide references to cavitation control and energy consumption optimization in piping systems using a perforated plate.